On the Necessity of Use in Russia a Differentiated Approach in Applying Methods of the Regulatory Impact Against of Different Types Territorial Formation - Dmitriy Yurevich Desyatnichenko; Olesya Yurevna Desyatnichenko (Управленческое консультирование)
The paper investigates the possibility and the necessity of using a differentiated approach to Russia in applying methods of the regulatory impact against territorial units of various types, considering foreign experience and existing problems in Russia unbalanced levels of socio-economic development of regions.